CORRELATION BETWEEN FINANCIAL LITERACY VARIABLES AND HOUSEHOLD SAVINGS BEHAVIOUR IN TWO SELECTED MUNICIPALITIES IN SOUTH AFRICA - Mbukanma, Ifeanyi; Rena, Ravinder (International Journal of Psychosocial Rehabilitation, 2021)
This study was conducted to ascertain financial literacy variables that have a statistically significant impact on household savings behaviour. Thus, to achieve this objective, financial literacy micro-variables were used to obtain quantitative data from the employees of the City of Tshwane and Mahikeng Municipality in South Africa. Correlation statistical analysis and factor analysis were performed to identify financial literacy micro-variables that have a significant impact on household savings behaviour as well as a confirmatory factor analysis through structural equation modelling. Hence, the findings of this study reveal that financial literacy variables under the domain of financial control, planning and knowledge have a positive correlation with determinant variables of South African household savings behaviour and recommend that stakeholders in charge of financial literacy and savings campaigns in South Africa should adopt the study’s contribution which identifies financial and savings literacy as core variables that can improve savings behaviour of South African households